Identification and characterization of popular rice (Oryza sativa L.) varieties through chemical tests - Nagendra, M.S.; Selvaraju, P.; Jerlin, R.; Ganesamurthy, K.; Senthil, N. (Journal of Phytology, 2020)
Identification and characterization of crop varieties are crucial for ensuring the genetic purity of seeds. The present investigation was carried out to identify suitable chemical methods that are fast, reliable and easy for seed analysts, breeders and seed producers for identification of a variety. Twenty-five popular rice varieties in the seed supply chain of Tamil Nadu were subjected to phenol, modified phenol, NaOH, aroma, gelatinization temperature (alkali spreading value), GA3 and 2,4-D tests. The results of the experiment revealed that phenol and modified phenol tests changed the colour of TKM 9 and TRY 1 variety to brown but no colour change was observed in the variety I.W. Ponni variety. The NaOH test is useful for the identification of TKM 9 variety as it changed the colourless solution to red. GA3 and 2,4-D tests characterized the varieties based on the shoot growth into two and three groups respectively. However, all the variety lacked aroma and exhibited a high gelatinization temperature.